2020
DOI: 10.3389/fcimb.2020.00156
|View full text |Cite
|
Sign up to set email alerts
|

Functional Identification and Structural Analysis of a New Lipoate Protein Ligase in Mycoplasma hyopneumoniae

Abstract: Mycoplasma hyopneumoniae (M. hyopneumoniae) is the causative agent of pandemic pneumonia among pigs, namely, swine enzootic pneumonia. Although M. hyopneumoniae was first identified in 1965, little is known regarding its metabolic pathways, which might play a pivotal role during disease pathogenesis. Lipoate is an essential cofactor for enzymes important for central metabolism. However, the lipoate metabolism pathway in M. hyopneumoniae is definitely unclear. Here, we identified a novel gene, lpl, encoding a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…A New Putative Lipoate-Protein Ligase Exists in M. hyopneumoniae Previously, we reported that Mhp-Lpl catalyzes the attachment of lipoic acid to the lipoyl domains of GcvH in vitro (Zhu et al, 2020). We wondered whether the lipoate modification of PdhD is catalyzed by Mhp-Lpl.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A New Putative Lipoate-Protein Ligase Exists in M. hyopneumoniae Previously, we reported that Mhp-Lpl catalyzes the attachment of lipoic acid to the lipoyl domains of GcvH in vitro (Zhu et al, 2020). We wondered whether the lipoate modification of PdhD is catalyzed by Mhp-Lpl.…”
Section: Resultsmentioning
confidence: 99%
“…Lipoate-protein ligases are responsible for the lipoate modification of these enzymes ( Reed et al, 1958 ). We previously reported that Mhp-Lpl of M. hyopneumoniae is a member of the lipoate-protein ligase family and can catalyze the lipoylation of M. hyopneumoniae GcvH in vitro ( Zhu et al, 2020 ). However, unexpectedly, Mhp-Lpl did not lipoylate PdhD, a lipoate-dependent subunit of M. hyopneumoniae ( Figure 3A ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lipoate protein ligase A (lplA) plays a role in the ligation of lipoic acid from host cells to the E2 subunit of the PDH complex to generate E2-lipoamide, which ultimately plays a crucial role in pyruvate metabolism [255]. lplA has been shown to be upregulated in the pathogenic 168 strain of M. hyopneumoniae [256].…”
Section: Dihydrolipoamide Dehydrogenase and Lipoate Protein Ligasementioning
confidence: 99%